Program Pemberdayaan Anak di LPKA Klas II Gunung Kidul, Yogyakarta - Aprilia Puji Hawa (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2021)
The coaching program for the inmates at the LPKA Class II Gunung Kidul, Yogyakarta is carried out with various programs. This program serves not only for coaching but also for empowering the inmates so that when they return to the community they will be easier to adapt to the skills they have acquired in LPKA. In this case, the writer conducted a research using descriptive qualitative methods and library research data collection techniques to collect as much information as possible relevant to the object of study, namely LPKA Class II Gunung Kidul, Yogyakarta. From the results of data collection, it was found that there are several empowerment programs for the inmates, namely Mental and Spiritual Development of Children, Fulfillment of Children's Basic Education Rights, Character Building of Children Through Theater Training, Music Training, Shoes Care Training, Making Training Booster,, Catfish Cultivation.